(3GdcJjHI GdcGefI ajef dbjfGg HGdCfOdS ef TYQGA GdeFI GdKGefIs - (3CHh YHO Gddg dSGf GdOjf eMeO Hf YHO Gddg Hf SYjO GHf GdNWjH GdZQfGWi GdCfOdSj,J (B776 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdCOH ai LejY eG ddafhf ef GdCShGb aGcgI TgjI GdCPhGb CeG HYOg , aEfi deG GSJhajJ aLeY gPG GdcJGH LedI hGaQI s
(3BNQgG (B:s
(3aeGPG YSi fgjI ef TcQ efYe jDda Hjf GdKhQ hGdVH LhOg cGf HGdCUd gfG eG fUg Edi gfG JhLO gPg GdcJjHI hdYd GdeDda eGJ bHd JeGegG GfJgi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B235s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B337 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B372 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 - (3U (B161 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B(141) s
Keywords: (3GdJGQjNs